Design of Maximum power Tracking System by Automatic Control of Solar Cell Panel to the Sun Direction - Kader H.A. Al-Shara (Journal of Madenat Alelem University College, 2018)
Renewable energy is an area of significant investment and importance for future generations. The basis of this project is to design a new automatic control system for solar panel that tracking maximum power tracking according to the direction of sun ray. This project is an analysis of maximum power that can generate from the solar panel. This project needed to investigate the system parameter that affected the input sun ray to the solar panel. The system parameter that needs to investigate is weather, cell type, number of cells, temperature and the intensity of the sun. The system parameter is important to create the maximum power that can be generated by the design solar panel. In this paper, the main purpose is to design a system which controls the direction of the solar panel base on the sun direction and the main system parameter is the intensity of sun in daily mode. The system uses the motor type for controlling the angle of the solar panel base on the maximum intensity of sun ray. The validity of this proposed system achieved the maximum power of 101 Watt compared with the conventional types.